HUBUNGAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN PEMECAHAN MASALAH SISWA PADA METODE PRAKTIKUM - Nelius Harefa (Jurnal Selaras : Kajian Bimbingan dan Konseling serta Psikologi Pendidikan, 2018)
This study aims to analyze the relationship between students' learning motivation with the student's ability in solving problems faced. By doing this analysis, the teacher will have additional input in determining the appropriate method of the learning process in the laboratory. This type of research is an experimental research. The hope of this study is that students who have high learning motivation will have high problem solving skills. The research data was collected by using test and observation instruments. Based on the results of the study, students' learning motivation has a significant relationship with student problem solving skills with probability or sig value. 0.012 <0.05. Students with high learning motivation (upper grade â‰¥ 70) had average problem solving skills of 75.8 while students with low learning motivation (lower class <70) had an average problem of problem solving skills of 58.6. Thus, it can be concluded that students who have high learning motivation will have better problem-solving skills than students who have low motivation to learn on practical methods. Keywords: problem solving skills, practice methods, learning motivation